Fire needling therapy for neurodermatitis: a systematic review and meta-analysis of randomized controlled trials - Qiu, Xiao; Hu, Xiangyu; Jia, Ruiling; Ding, Yuting; Wang, Yuyi (Frontiers in Medicine, 2025)
ObjectiveThis meta-analysis aimed to evaluate the clinical effectiveness and safety of fire needling therapy for neurodermatitis, either as monotherapy or in combination with conventional treatments.MethodsFollowing PRISMA 2020 guidelines, randomized controlled trials were systematically searched across Chinese and English databases up to October 2024. Ten RCTs involving 868 patients were included. Outcomes assessed included effectiveness rate, recurrence rate, pruritus scores, inflammatory cytokine levels, Dermatology Life Quality Index (DLQI), and adverse events. Data were analyzed using RevMan 5.4.1, with effect sizes expressed as risk ratios or mean differences.ResultsFire needling monotherapy showed no significant superiority over conventional treatment in effectiveness rates (p > 0.05). However, combined therapy demonstrated significantly higher effectiveness at the >90% threshold after 4 weeks (RR: 2.04, 95% CI: 1.61–2.59) and reduced recurrence rates within 6 months after 2-week treatment (RR: 0.36, 95% CI: 0.14–0.93). Combined therapy also improved DLQI scores (MD: −3.91, 95% CI: −6.15 to −1.67) and reduced pruritus (MD: −0.25, 95% CI: −0.43 to −0.07) and inflammatory markers (TNF-α, IL-4, IL-6, IL-8, IgE; p  0.05). Adverse events were mild.ConclusionFire needling therapy combined with conventional treatment may enhance therapeutic outcomes for neurodermatitis, particularly in reducing pruritus, improving quality of life, and modulating inflammation. However, limitations include methodological flaws in included studies and regional publication bias. Higher-quality RCTs are needed to validate these findings and clarify long-term effectiveness.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024617150, identifier CRD42024617150.